P45 Assessment of bleeding risk in patients diagnosed with Pulmonary Embolism at diagnosis and follow-up: a service evaluation at a large regional hospital. (11th November 2022) - Bhatnagar, M; Burke, K; Roy, A; Musgrave, K; Simpson, AJ; Rostron, A
Abstract : Introduction: Bleeding risk assessment in patients anticoagulated for venous thromboembolism (VTE) is important at treatment initiation to guide optimal anticoagulant choice, duration, and dose. Risk stratification of pulmonary embolism (PE) alongside bleeding risk at diagnosis can help personalise management. We evaluated risk stratification of PE and assessment of bleeding risk in a large regional hospital. Methods: We screened all CT Pulmonary Angiograms (CTPA) performed over a 3-month period and included those positive for PE. Data was collected on the number of patients receiving thrombolysis for PE, those anticoagulated (including choice and duration of agent), documented assessment of bleeding risk at initiation and follow up, and any adverse bleeding events. We retrospectively calculated sPESI, VTE-BLEED and HASBLED scores for each patient. Results: Over 3 months, 480 patients underwent CTPA. 87/480 (18%) had PE; age range 18 to 90 years, median 67. 56 had peripheral PE, 27 central and 4 both. 4/87 (4.6%) were thrombolysed (one with half-dose thrombolysis). All thrombolysed patients had an assessment of PE severity performed to aid risk stratification; 2/4 were haemodynamically unstable, 1/4 had sPESI calculated, 3/4 had troponin measured and all four had investigation for RV dysfunction on echocardiography or CTPA prior to receiving thrombolysis. An additional patient was considered for thrombolysis but did not receive this due to contraindications. All 87 patients received anticoagulation (DOAC 73%, LMWH 17%, warfarin 10%). 58/87 (66%) were not counselled on anticoagulation at treatment initiation. 6/87 patients died during admission and 2 were lost to follow-up. A bleeding risk score was not performed in 85/87 (97%) at treatment initiation and in 79/79 (100%) at follow-up. Four patients had a clinical assessment of bleeding risk at follow-up. Six patients had adverse bleeding events, three were major and three were clinically relevant non-major episodes. Conclusions: Most patients were not counselled at initiation of anticoagulation and did not have bleeding risk assessments at initial or follow-up visits. Bleeding risk scores are an objective, albeit unvalidated, method of assessment and can help individualise management of PE.